int x^2/(x^4-2x^2-8)dx
To solve using partial fraction method, the denominator of the integrand should be factored.
x^2/(x^4-2x^2-8)=x^2/((x-2)(x+2)(x^2+2))
If the factor in the denominator is linear, its partial fraction has a form A/(ax+b) .
If the factor is quadratic, its partial fraction is in the form (Ax+B)/(ax^2+bx+c) .
So, expressing the integrand as sum of fractions, it becomes:
x^2/((x-2)(x+2)(x^2+2)) = A/(x-2) + B/(x + 2) + (Cx + D)/(x^2+2)
To determine the values of A, B, C and D, multiply both sides by the LCD of the fractions present
(x-2)(x+2)(x^2+2)*x^2/((x-2)(x+2)(x^2+2)) = (A/(x-2) + B/(x + 2) + (Cx + D)/(x^2+2))*(x-2)(x+2)(x^2+2)
x^2=A(x+2)(x^2+2) + B(x-2)(x^2+2) + (Cx+D)(x-2)(x+2)
Then, assign values to x in which either x-2,x+2 orx^2+2will become zero.
So plug-in x=2 to get the value of A.
2^2=A(2+2)(2^2+2) + B(2-2)(2^2+2) + (C*2+D)(2-2)(2+2)
4=A(24)+B(0)+(2C+D)(0)
4=24A
1/6=A
Plug-inx=-2 to get the value of B.
(-2)^2=A(-2+2)((-2)^2+2) + B(-2-2)((-2)^2+2) + (C(-2)+D)(-2-2)(-2+2)
4=A(0)+B(-24) + (-2C+D)(0)
4=-24B
-1/6=B
To solve for D, plug-in the values of A and B. Also, set the value of x to zero.
0^2 =1/6(0+2)(0^2+2) + (-1/6)(0-2)(0^2+2) + (C(0)+D)(0-2)(0+2)
0=2/3+2/3-4D
0=4/3-4D
4D=4/3
D=1/3
To solve for C, plug-in the values of A, B and D. Also, assign any value to x. Let it be x=1.
1^2=1/6(1+2)(1^2+2)+( -1/6)(1-2)(1^2+2) + (C(1)+1/3)(1-2)(1+2)
1=3/2 +1/2+(C+1/3)(-3)
1=3/2+1/2-3C -1
1=1-3C
0=-3C
0=C
So the partial fraction decomposition of the integrand is:
int x^2/(x^4-2x^2-8)dx
=intx^2/((x-2)(x+2)(x^2+2))dx
=int (1/(6(x-2)) - 1/(6(x + 2)) + 1/(3(x^2+2)))dx
Expressing it as three integrals, it becomes
= int 1/(6(x-2))dx - int 1/(6(x+2))dx + int 1/(3(x^2+2))dx
= 1/6 int1/(x-2)dx - 1/6 int1/(x+2)dx + 1/3 int 1/(x^2+2)dx
For the first and second integral, apply the formula int 1/u du = ln|u|+C .
And for the third integral, the formula isint 1/(u^2+a^2)du =1/a tan^(-1)(u/a)+C .
=1/6ln|x-2| - 1/6ln|x+2| + 1/3*1/sqrt2 tan^(-1)(x/sqrt2)+C
=1/6ln|x-2| - 1/6ln|x+2| + 1/(3sqrt2) tan^(-1)(x/sqrt2)+C
=1/6ln|x-2| - 1/6ln|x+2| + sqrt2/6 tan^(-1)((xsqrt2)/2)+C
Therefore, int x^2/(x^4-2x^2-8)dx=1/6ln|x-2| - 1/6ln|x+2| + sqrt2/6 tan^(-1)((xsqrt2)/2)+C .
Monday, January 6, 2020
int x^2/(x^4-2x^2-8) dx Use partial fractions to find the indefinite integral
Subscribe to:
Post Comments (Atom)
Why is the fact that the Americans are helping the Russians important?
In the late author Tom Clancy’s first novel, The Hunt for Red October, the assistance rendered to the Russians by the United States is impor...
-
The poem contrasts the nighttime, imaginative world of a child with his daytime, prosaic world. In the first stanza, the child, on going to ...
-
There are a plethora of rules that Jonas and the other citizens must follow. Again, page numbers will vary given the edition of the book tha...
-
The given two points of the exponential function are (2,24) and (3,144). To determine the exponential function y=ab^x plug-in the given x an...
-
Robinson Crusoe, written by Daniel Defoe, is a novel. A novel is a genre defined as a long imaginative work of literature written in prose. ...
-
Hello! This expression is already a sum of two numbers, sin(32) and sin(54). Probably you want or express it as a product, or as an expressi...
-
The title of the book refers to its main character, Mersault. Only a very naive reader could consider that the stranger or the foreigner (an...
-
The only example of simile in "The Lottery"—and a particularly weak one at that—is when Mrs. Hutchinson taps Mrs. Delacroix on the...
No comments:
Post a Comment